Effect of Energycane Integration on Ground-Dwelling Arthropod Biodiversity in a Sugarcane-Sweet Corn Cropping System - Amandeep Sahil Sharma; Ricardo A. Lesmes-Vesga; Simranjot Kaur; Hardeep Singh; Hardev Singh Sandhu (Agronomy)
Integrating bioenergy crops into existing agricultural systems may influence soil biodiversity, yet evidence remains limited for second-generation bioenergy crops such as energycane. This study examined the impact of energycane integration on soil arthropod communities in the Everglades Agricultural Area, Florida, compared to traditional sugarcane and sweetcorn cropping systems. Over two crop cycles (plant cane and first ratoon), soil arthropod abundance and diversity were assessed using pitfall traps. Energycane and sugarcane, both perennial crops, showed no significant differences in order richness or Shannon diversity. Similarly, when energycane was compared with sugarcane and sweetcorn (during the first sampling), it had similar arthropod abundance. However, sweetcorn remained fallow in the second and third samplings, attracting arthropods like fire ants and earwigs, particularly due to pigweed. Diversity metrics based on Hill numbers revealed a decline in the effective abundance of ground-dwelling arthropods with increasing diversity order, influenced by differences in sampling duration. Importantly, no previous studies have been found that have reported on the effects of energycane integration into the existing cropping system on soil arthropod biodiversity. These findings highlight that energycane supports biodiversity levels comparable to sugarcane cropping systems with no negative impacts on soil arthropod abundance. This study underscores the need to consider soil biodiversity impacts when evaluating sustainable bioenergy crop transitions and the potential ecological trade-offs of perennial cropping systems.